Nanoporous Gold Films as Catalyst - 김상훈 (2016)
Nanoporous gold (NPG) is reviewed as a catalyst. Various preparation methods were first reviewed for NPG and its structure. Applications of this catalyst in CO oxidation, hydrogen oxidation, hydrogen production are discussed. Regarding CO oxidation, detailed studies on reaction mechanism and density functional theory (DFT) calcula tions were also reviewed. Not only as a model reaction but also practical aspects of removing CO residue in hydrogen stream are discussed. Beyond those simple reactions, the application of NPG to more complicated reactions such as alcohol oxidation is reviewed. Selective aerobic oxidation of gasphase alcohols is first reviewed and reactions in liquid phase are discussed. Finally, future prospects of NPG as a catalyst for more complicated reactions such as organic synthesis are briefly discussed.